How Does Information Technology Capabilities Impacr on SMEs? In Sights From Literatur Review - Rahmahdiyyah, Tsabitah; Pujianto, Wahyu Eko; Qurrotu'aini, Nafia Ilhama; Kamila, Edita Rachma (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The purpose of this study is to systematically review the existing literature on information technology capability (ITC). This research uses the systematic literature review (SLR) method based on phenomena that are answered from various studies sourced from journals that have been published following current developments related to information technology capability. This study searched all research on ITC from 1993 to 2024, found 167 articles, and used 74 articles from Scopus. The results of this study indicate that ITC offers great opportunities and has a positive impact on SMEs, but support from the government and related institutions is needed to overcome the challenges, so that SMEs can optimally utilize technology for business growth and sustainability. Therefore, this study concludes that the relationship between the antecedents and consequences of ITC shows the importance of the factors that influence ITC. By understanding and developing the right antecedents and consequences, organizations can leverage ITC to survive in increasingly complex and dynamic markets.